2020
DOI: 10.3390/molecules25246009
|View full text |Cite
|
Sign up to set email alerts
|

The First Nickelacarborane with closo-nido Structure

Abstract: The first nickelacarborane with closo-nido structure [10′,11′-(Py)2-3,9′-Ni(1,2-C2B9H11)(7′,8′-C2B8H8)] was isolated from the reaction of nickel(IV) bis(dicarbollide) with pyridine. The molecular structure of this complex was determined by single crystal X-ray diffraction. The nickel atom is a common vertex for the closo-NiC2B9 cluster and the nido-NC2B8 cluster where it is located together with carbon atoms in the open NiC2B2 pentagonal face. It is assumed that its formation proceeds through the nucleophile-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Despite its more than 50 year history, the chemistry of nickelacarboranes has received much less development compared to the chemistry of cobalta- and ferracarboranes, which are characterized by the formation of extremely stable bis­(dicarbollide) complexes, as well as the chemistry of rhoda- and ruthenacarboranes, , which are widely studied as catalysts for various processes. This is largely due to the increased tendency of nickelacarboranes to skeletal rearrangements, as well as the often uninformative 11 B NMR spectra of nickelacarboranes, which makes their identification problematic. Certain problems are also associated with the lack of methods for modifying nickel bis­(dicarbollide) and its reduced stability , compared to iron and cobalt bis­(dicarbollides). Nevertheless, some nickelacarboranes demonstrate good prospects for use in material science as a key component of redox-controlled molecular motors, a fast redox shuttle for dye-sensitized solar cells, electroconductive materials, , as well as in catalysis. , …”
Section: Introductionmentioning
confidence: 99%
“…Despite its more than 50 year history, the chemistry of nickelacarboranes has received much less development compared to the chemistry of cobalta- and ferracarboranes, which are characterized by the formation of extremely stable bis­(dicarbollide) complexes, as well as the chemistry of rhoda- and ruthenacarboranes, , which are widely studied as catalysts for various processes. This is largely due to the increased tendency of nickelacarboranes to skeletal rearrangements, as well as the often uninformative 11 B NMR spectra of nickelacarboranes, which makes their identification problematic. Certain problems are also associated with the lack of methods for modifying nickel bis­(dicarbollide) and its reduced stability , compared to iron and cobalt bis­(dicarbollides). Nevertheless, some nickelacarboranes demonstrate good prospects for use in material science as a key component of redox-controlled molecular motors, a fast redox shuttle for dye-sensitized solar cells, electroconductive materials, , as well as in catalysis. , …”
Section: Introductionmentioning
confidence: 99%
“…B 12 H 12 2− is particularly stable and can thus also act as a detrimental thermodynamic sink for further dehydrogenation reactions. The properties of closo-hydroborates and related anions were addressed in several recent publications [6,[25][26][27][28]. New research on the thermal properties of closo-hydroborate salts revealed a high-temperature phase transition in Na 2 B 12 H 12 leading to a superionic phase [29].…”
Section: Introductionmentioning
confidence: 99%